In‐hospital cost analysis of prostatic artery embolization compared with transurethral resection of the prostate: post hoc analysis of a randomized controlled trial. (28th January 2019) - Müllhaupt, Gautier; Hechelhammer, Lukas; Engeler, Daniel S.; Güsewell, Sabine; Betschart, Patrick; Zumstein, Valentin; Kessler, Thomas M.; Schmid, Hans‐Peter; Mordasini, Livio; Abt, Dominik
Abstract : Objectives: To perform a post hoc analysis of in‐hospital costs incurred in a randomized controlled trial comparing prostatic artery embolization (PAE) and transurethral resection of the prostate (TURP). Patients and Methods: In‐hospital costs arising from PAE and TURP were calculated using detailed expenditure reports provided by the hospital accounts department. Total costs, including those arising from surgical and interventional procedures, consumables, personnel and accommodation, were analysed for all of the study participants and compared between PAE and TURP using descriptive analysis and two‐sided t ‐tests, adjusted for unequal variance within groups (Welch t ‐test). Results: The mean total costs per patient (±sd ) were higher for TURP, at €9137 ± 3301, than for PAE, at €8185 ± 1630. The mean difference of €952 was not statistically significant ( P = 0.07). While the mean procedural costs were significantly higher for PAE (mean difference €623 [ P = 0.009]), costs apart from the procedure were significantly lower for PAE, with a mean difference of €1627 ( P < 0.001). Procedural costs of €1433 ± 552 for TURP were mainly incurred by anaesthesia, whereas €2590 ± 628 for medical supplies were the main cost factor for PAE. Conclusions: Since in‐hospital costs are similar but PAE and TURP have different efficacy and safety profiles, the patient's clinical condition and expectations – rather than finances – should be taken into account when deciding between PAE and TURP.